Character Education : Thoughts of Prof. Dr. Hamka and Ki Hadjar Dewantara (Pendidikan Budi Pekerti : Pemikiran Prof Dr Hamka dan Ki Hadjar Dewantara - Muhammad Agung Kurniawan; Imam Syafe'i; Bambang Sri Anggoro (Shautut Tarbiyah, 2023)
Character education has the same essence and meaning as moral education and moral education. The goal is to shape the child's personality so that he becomes a good human being, a citizen, and a good citizen. Here it can be seen that moral education is important, but there is a lack of implementation of moral education. Even though we know that education in Indonesia at every level of education is accompanied by ethics subjects. Character or moral education plays an important role in life, both individually and collectively, so Allah SWT is revealed to the Messenger of Allah to provide moral education to his family, friends, and followers. As it is known that the mission of the Messenger was sent to perfect the morals or character of mankind. This study uses historical and philosophical approaches, while the type of research is library research. The data collection technique used is a literature study. The results of the author's analysis of the thoughts of Hamka and Ki Hajar Dewantara that character education and the formation of the character of the nation's children are the responsibility of the school, family, and community environment.Keywords: Character Education